Relación entre el índice de precios al consumidor de Loreto con el tipo de cambio nominal del 2010 al 2020 - Mejia Perez, Braddyck Esteban (2023)
The present investigation determines the type of relationship between the Loreto consumer price index with the nominal exchange rate during the period from 2010 to 2020, in addition; determines the variation of the Loreto consumer price index and the nominal exchange rate and the degree of correlation between the Loreto consumer price index with the nominal exchange rate. is also determined. The research methodology is quantitative and non-experimental design and due to the periodicity of the study, it’s considered research with a longitudinal design type. In the results, Specific Hypothesis 1 is accepted: The variation of the Loreto consumer price index is positive. Likewise, Specific Hypothesis 2 is Accepted: The variation of the nominal exchange rate is positive during the period from 2010 to 2020. General Hypothesis is accepted: The relationship between the Loreto consumer price index is directly proportional to the type of nominal exchange rate, with the correlation coefficient is 0.877446632, being between 0≤R^ 2≤1 and Specific Hypothesis 3 is Rejected: The degree of correlation between the Loreto consumer price index with the nominal exchange rate is excellent, whose determination coefficient is 0.769912592 which.